Developing geometric thinking through culturally contextualized mathematical modeling: a yurt-building lesson for middle-school students in Kazakhstan - Kazimova, Dinara; Sadykova, Saltanat; Kostangeldinova, Alma; Tazhigulova, Gulmira; Shertser, Alexander (Frontiers in Education, 2025)
This mixed-methods study examines the impact of a single culturally contextualized STEAM lesson, constructing a scale model of a Kazakh yurt, on sixth-grade students’ geometry confidence and cultural awareness. Forty-four students (aged 11–12) from a public school in East Kazakhstan participated in the hands-on activity during a 45-min mathematics period. Data sources included (i) a post-lesson perception survey (Likert, multiple-choice, open-ended), (ii) teacher field notes, and (iii) photographs of student artifacts. Reliability of the six-item Likert scale was acceptable (Cronbach’s α = 0.81). Descriptive statistics show that students’ self-rated confidence in measuring polygon sides (M = 3.48, SD = 1.17) and applying perimeter formulas (M = 3.61, SD = 1.26) fell in the moderate range, while appreciation for Kazakh cultural heritage was high (Yes = 52.3%; Partially = 29.5%). Thematic analysis of 176 open-ended responses, with 92% intercoder agreement, revealed three recurring themes: (1) recognizing geometry in everyday artifacts, (2) difficulties visualizing the transition from 2D plans to a 3D dome, and (3) heightened respect for nomadic engineering ingenuity. Although the study relies on post-lesson self-report rather than pre- and post-objective testing, the triangulated evidence suggests that a single culturally grounded project can foster meaningful, if preliminary, gains in geometric thinking and cultural connectedness. Limitations include the brief intervention window and single-site design; future work should incorporate objective assessments and multi-lesson sequences to substantiate learning outcomes.